Relationship of Sighting Ocular Dominance with Macular Photostress Test Time and Thickness of the Middle Macular Layers - Pekel, Gökhan; Akbulut, Selen; Pekel, Evre; Çetin, Ebru Nevin (Optometry and vision science, 2021)
The mechanisms of sighting ocular dominance, which is particularly important in monovision therapies and sports vision, are not fully understood yet. Whether the macula affects ocular dominance or ocular dominance affects the macula is also a subject of interest. The aim of this study was to investigate the relationship of sighting ocular dominance with macular photostress test time and middle macular layer thickness. One-hundred eyes of 50 healthy adult volunteers were included in this cross-sectional study. Sighting eye dominance was decided by a hole-in-the-card test. The macular photostress test was performed by exposing the eye to the ophthalmoscope light for 10 seconds and measuring the time taken to return to visual acuity within one row of pre-light exposure acuity. The spectral-domain optical coherence tomography examinations were performed to measure thickness of middle macular layers (i.e., outer nuclear, outer plexiform, inner nuclear, and inner plexiform). Refractive error and intraocular pressure (IOP) measurements were also recorded. The comparison of dominant and nondominant eyes in the aspect of refractive error, IOP, and macular photostress test time did not show statistically significant differences (P > .05). The thicknesses of macular outer nuclear, outer plexiform, inner nuclear, and inner plexiform layers were similar in the dominant and nondominant eyes (P > .05). In addition, macular photostress time was not statistically significantly correlated with the thickness of middle macular layers (P > .05). The thickness of middle macular layers and macular photostress recovery time are similar in dominant and nondominant eyes.